REVITALISASI PENDIDIKAN ISLAM DALAM PERSPEKTIF KIAI HASYIM ASY’ARI - Khoiriyah, Rizka (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2017)
This study discusses the revitalization of Islamic Education during the period of colonialism in the perspective of Kiai Hasyim Asy'ari, In order to know the extent to which various changes and developments in Islamic education should duly make us always encouraged to review and improve again the quality of self, for the improvement of quality and quantity of education Islam in Indonesia. Because basically Dari since the state of Indonesia was born in 1945, education has been the basis of one of the milestones of the nation's progress. Education is like a uterus in which there are genes with a neat composition with all the seeds of existing capabilities. Therefore there is a need for motivation in the business of potential excavation, direction and good planning in the development of education. From the results of research conducted do indicate from some thoughts K.H Hasyim Ash'ari who talked about education more emphasis on ethics education. Because ethics is more important than intelligence. Expertise in hadiths colored in the aspect of the education. In order for some of his work to change the situation at that time and experience a rapid change and development of an education.Â